Lithium modifies brain arachidonic and docosahexaenoic metabolism in rat lipopolysaccharide model of neuroinflammation - Basselin, Mireille (The American Society for Biochemistry and Molecular Biology, 2010)
Neuroinflammation, caused by 6 days of intracerebroventricular infusion of a low dose of lipopolysaccharide (LPS; 0.5 ng/h), stimulates brain arachidonic acid (AA) metabolism in rats, but 6 weeks of lithium pretreatment reduces this effect. To further understand this action of lithium, we measured concentrations of eicosanoids and docosanoids generated from AA and docosahexaenoic acid (DHA), respectively, in high-energy microwaved rat brain using LC/MS/MS and two doses of LPS. In rats fed a lithium-free diet, low (0.5 ng/h)- or high (250 ng/h)-dose LPS compared with artificial cerebrospinal fluid increased brain unesterified AA and prostaglandin E(2) concentrations and activities of AA-selective Ca(2+)-dependent cytosolic phospholipase A(2) (cPLA(2))-IV and Ca(2+)-dependent secretory sPLA(2). LiCl feeding prevented these increments. Lithium had a significant main effect by increasing brain concentrations of lipoxygenase-derived AA metabolites, 5- hydroxyeicosatetraenoic acid (HETE), 5-oxo-eicosatetranoic acid, and 17-hydroxy-DHA by 1.8-, 4.3- and 1.9-fold compared with control diet. Lithium also increased 15-HETE in high-dose LPS-infused rats. Ca(2+)-independent iPLA(2)-VI activity and unesterified DHA and docosapentaenoic acid (22:5n-3) concentrations were unaffected by LPS or lithium. This study demonstrates, for the first time, that lithium can increase brain 17-hydroxy-DHA formation, indicating a new and potentially important therapeutic action of lithium.